Effectiveness Analysis of an Ecolliteracy-Based Fiqh Instructional Design Developed through the Plomp Model - Mustamin Siregar; Rusydi Ananda; Solihah Titin Sumanti (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2025)
This study aims to develop and evaluate the validity, practicality, and effectiveness of an ecoliteracy-based Fiqh learning design for Islamic Junior High Schools (Madrasah Tsanawiyah). This study uses the Plomp development model, which includes the initial investigation, design, construction, and evaluation phases. The research participants were 32 students of MTs Negeri I Tapanuli Selatan. Data were collected through validation sheets, observation sheets, and learning outcome tests, and analyzed using expert assessment, practitioner evaluation, and t-test. The research findings indicate that the learning design was assessed as appropriate by experts (M = 3.48) and very appropriate by practitioners (M = 3.52). The practicality assessment showed an average score (M = 3.31). The effectiveness test showed a significant increase in student learning outcomes (t = 4.26, p < 0.05) with a moderate N-Gain of 0.38. These results indicate that the ecoliteracy-based Fiqh learning design is valid, practical, and effective. This design can serve as an innovative learning resource to support the integration of ecological literacy into Fiqh education.